Anjung Rimbun: revitalisation of al-Ghazali road and SHAS mosque lower courtyard - Yusof, Zeenat Begam; Mohd. Din, Shamzani Affendy; Mohd. Yaman, Maheran; Mohyin, Nur Affah; Mohamad Suhaimi, Mohamad Saifulnizam (IIUM Press, 2023)
Re-vitalization of Al-Ghazali Road and SHAS Mosque Lower Courtyard project is conducted to mitigate the flood and create genus loci for Al-Ghazali Road, located in the IIUM Gombak Campus. The project consists of three parts: the walkway, courtyard and backyard. The design of the architectural elements adopted the traditional Malay architecture of the state of Pahang. The overall concept of the project is known as Anjung Rimbun. The synergy of all architectural and landscape elements brings the essence of Malay traditional architecture.